Integral humanism according to Pope Francis - Valadier, Paul (Razón y fe, 2020)
In his encyclical letter Laudato si’, Pope Francis refers to “an integral humanism”. What does this expression mean? We must clarify its meaning to avoid making a fundamentalist misreading, derived from the defense of narrow principles. Pope Francis contributes to an interpretation of humanism, extended to the service of the common home and, therefore, of the common good.